Non-O1, Non-O139 Vibrio cholerae Bacteremia in an Autoimmune Pancreatitis Patient - Gu, Cheng-Jing; Ding, Ming-Dong; Zhou, Da-Ming; Li, Jie; Yu, Wen-Qing; Yang, Yong-Lin (Case Reports in Infectious Diseases, 2024)
Over 200 different serogroups of Vibrio cholerae based on O-polysaccharide specificity have been described worldwide, including the two most important serogroups, O1 and O139. Non-O1/non-O139 V. cholerae serogroups generally do not produce the cholera-causing toxin but do sporadically cause gastroenteritis and extra-intestinal infections. Recently, however, bloodstream infections caused by non-O1/non-O139 V. cholerae are being increasingly reported, and these infections are associated with high mortality in immunocompromised hosts. We describe a case of non-O1/non-O139 V. cholerae bacteremia in a patient with autoimmune pancreatitis and stenosis of the intra- and extrahepatic bile ducts. The clinical manifestations of bacteremia were fever and mild digestive symptoms. The blood cultures showed V. cholerae, which was identified as a non-O1, non-O139 serogroup by slide agglutination tests and PCR. The bloodstream infection of the patient was likely caused by the consumption of contaminated seafood at a banquet. The patient recovered after the administration of a third-generation cephalosporin. Non-O1/non-O139 V. cholerae infection presents with or without gastrointestinal manifestations; close attention should be paid to the possibility of disseminated non-O1/non-O139 V. cholerae infection in high-risk patients.